Statistical methods for psychology - Howell, David C. (Thomson Wadsworth, 2010)
This edition continues to focus students on two key themes: the importance of looking at the data before beginning a hypothesis test, and the importance of knowing the relationship between the statistical test in use and the theoretical questions being asked by the experiment